Kemajuan Desa dan Produk Unggulan Pertanian di Kabupaten Bombana Sulawesi Tenggara - Amir, Azhar (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
The aims of this study were to identify the status of village progress based on the value of the village development index (IDM) and to identify the leading commodity in the agricultural sector in Bombana Regency. The main data of this study are secondary data of villages IDM, which were sourced from The Ministry of Villages, Disadvantaged Areas Development and Transmigration, agricultural production in Bombana Regency and Southeast Sulawesi Province, which were sourced from the Central Statistics Board of Indonesia. The Data were analyzed using descriptive and quantitative analysis methods, namely composite index analysis of IDM and location Quotient (LQ) analysis The data showed a village that has progressed to become a developed village namely Waemputtang Village with an index value of 0.7335. The leading food crop products are rice plants. there are 18 districts in Bombana Regency which produce rice. the types of livestock that are surplus and progressive in Bombana are cows, buffaloes, native chickens. These leading commodities already have a value of LQ > 1